Simulation-based vulnerability assessment in transit systems with cascade failures - Chen, Hongyu (2022)
The urban transit system is vulnerable to various types of hazards and failures, where the failure of a system component may lead to a redistribution of the pressure and result in cascade failures. It is of great significance to develop an efficient approach to model and assess the system vulnerability for achieving a sustainable transit system. This research develops a novel holistic approach to assess the vulnerability of the urban transit system toward sustainable development. The cascading failure mechanism is incorporated in the established complex network to simulate the process in a dependent system, where the failure of one or a few system components can trigger the failure of other components. Several attack strategies (i.e., static and dynamic intentional attack and random attack strategies) are used to test the system vulnerability, and the impacts of the tolerance parameter and passenger transfer rate on the loss of transport capacity are explored. A complex network consisting of 198 nodes and 415 edges is constructed to model the urban transit system with cascade failures. A realistic urban transit system in China is used as a case to testify the applicability and effectiveness of the developed approach. Results indicate that: (1) The interchange stations display high vulnerability in the network and Xianggang Rd station, Hongtu Boulevard station, Taipingyang station, and Zhongnan Rd are the most vulnerable stations, which should be paid more attention in the operation management; (2) The damage of the attacks in the intentional attack strategies are much more significant than that in the random attack, indicating that the proposed approach presents the ability to identify the important nodes; (3) The metric of node betweenness would be more efficient to identify the vulnerable nodes in the intentional attack; (4) The optimal value of the tolerance parameter is the range [0.8, 0.9], while keeping the passenger transfer rate in the range [0.3, 0.4] can effectively reduce the effect of cascade failures with minimum resources. The developed approach can be used as a decision tool to not only assess the vulnerability in the existing transit system but also optimize the planning of the new transit system.